As a science of fossils - Tillería Aqueveque, Leopoldo (Razón y fe, 2026)
This paper analyzes the pictorial work of contemporary Japanese artist Nobu Okanoya. To this end, the paper employs the paradigmatic case method (Flyvbjerg, 2006) and a brief framework based on Kant’s teleological theory. Two of the Japanese artists’ works are analyzed that simulate the presentation of two fossils from a particular geological era of the planet. This simulation exhibits such a degree of perfection, including a certain organizing logos, that the artist’s simulation is entirely plausible, thereby transforming the analyzed works into a performance halfway between science and art. In a true artistic teleology, Okanoya, deliberately or not, resorts to the famous concept of “as if” to create a figurative-hyperrealist work in the fossil painting subgenre, that seems to fuse aisthesis and episteme. The conclusions confirm the initial hypothesis, that is, that, in the midst of post-postmodernity, the possible encounters between science and art remain to be discovered and, above all, to be admired.